2022
DOI: 10.1038/s42004-022-00785-2
|View full text |Cite
|
Sign up to set email alerts
|

Using genetic algorithms to systematically improve the synthesis conditions of Al-PMOF

Abstract: The synthesis of metal-organic frameworks (MOFs) is often complex and the desired structure is not always obtained. In this work, we report a methodology that uses a joint machine learning and experimental approach to optimize the synthesis conditions of Al-PMOF (Al2(OH)2TCPP) [H2TCPP = meso-tetra(4-carboxyphenyl)porphine], a promising material for carbon capture applications. Al-PMOF was previously synthesized using a hydrothermal reaction, which gave a low throughput yield due to its relatively long reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…A genetic algorithm was used by Domingues et el. to systematically search for the optimal synthesis conditions of Al-PMOF, and excellent crystallinity and yield close to 80% were shown in a short reaction time in just two generations . Kitamura et al used a data-driven approach to visually map the previously reported synthesis conditions for anionic lanthanide-based MOFs, revealed the existence of unexplored search spaces, and then synthesized a series of new MOFs .…”
Section: Machine Learning For Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…A genetic algorithm was used by Domingues et el. to systematically search for the optimal synthesis conditions of Al-PMOF, and excellent crystallinity and yield close to 80% were shown in a short reaction time in just two generations . Kitamura et al used a data-driven approach to visually map the previously reported synthesis conditions for anionic lanthanide-based MOFs, revealed the existence of unexplored search spaces, and then synthesized a series of new MOFs .…”
Section: Machine Learning For Mofsmentioning
confidence: 99%
“…to systematically search for the optimal synthesis conditions of Al-PMOF, and excellent crystallinity and yield close to 80% were shown in a short reaction time in just two generations. 78 Kitamura et al used a data-driven approach to visually map the previously reported synthesis conditions for anionic lanthanidebased MOFs, revealed the existence of unexplored search spaces, and then synthesized a series of new MOFs. 79 The importance of abandoned synthesis data was also emphasized by Hu et al and shown to benefit the ML predictions of C 2 H 2 , C 2 H 4 , and CO 2 adsorption in anion-pillared MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although Al-PMOF was proven to be exceptional in CO 2 capture and was successfully synthesized, it had low yields (38%–88%) and required a long reaction time (16 h). To tackle this inefficiency problem, synthesis conditions for Al-PMOF were optimized using the parameters of both failed and partially successful experiments …”
Section: Ai Applications Of Porous Materials For Co2 Capturementioning
confidence: 99%
“…The good samples (green) have crystallinity scores larger than 6 out of 10 with yields larger than 50%, while the poor and bad samples (yellow/orange and brown) have crystallinity scores less than 6 out of 10 and yields less than 50%. Readapted with permission from ref .…”
Section: Ai Applications Of Porous Materials For Co2 Capturementioning
confidence: 99%
See 1 more Smart Citation